Link between Internet addiction and depression and roles of social withdrawal and school belonging. - Wang, Zhiyou; Ye, Yajun; Li, Chunkai (Child & Family Social Work, 2024)
Depression and Internet addiction are common public health problems among adolescents. Previous literature has examined this association, but its underlying mechanisms remain unclear. The present study aims at identifying the influencing mechanisms of this association by constructing a moderated mediation model focusing on social withdrawal and school belonging. A sample of 616 Chinese middle and high school adolescents are surveyed regarding Internet addiction, depression, social withdrawal and school belonging. The Macro PROCESS was used to examine the proposed theoretical model. Results reveal that social withdrawal partially mediates the nexus between Internet addiction and adolescent depression. In addition, school belonging significantly moderates the association of social withdrawal with adolescent depression. These findings may guide future prevention and intervention strategies for depressed teenagers affected by Internet addiction.